THE CHARACTER AND THEME IN “ALADDIN” MOVIE FROM WALT DISNEY 2019 BY GUY RITCHIE - Popon Parnuningsih; Hasbullah Hasbullah (Universitas Indraprasta PGRI, 2019)
Abstract: The purpose of the research is to find out the character and theme in the “Aladdin” movie from Walt Disney 2019 by Guy Ritchie. This research is designed as qualitative research. The data are collected by analyzing the data found in the film. The analysis of the film is undertaken on the dialogues. The result of the research is the form of character and theme. 1) The character which emerges in film “Aladdin”, Protagonist is 65%, Antagonist is 29%, and Foil 6%. It means that the protagonist is dominating. 2) Theme that exist in the film, Complexity of Human Relationship gets 35%, Moral implication is 23,333%, Social Problem is 18,333%, Struggle for Human Dignity is 10%, Truth of Human Nature is 5%, Coming of Age/ Loss of Innocence/ Growing Awareness is 5%, Moral or Philosophical Riddle is 3,333%. It means that complexity of human relationship is dominating.Key Words: character; theme; movie; Walt Disney.